HUBUNGAN KUALITAS PELAYANAN DENGAN KEPUASAN PASIEN RAWAT INAP DI PUSKESMAS DPT CIKALONGWETAN TAHUN 2019 - Ayu Laili Rahmiyati; Gunawan Irianto; Asep Dian Abdillah; Suhat; Endah Nursyahyanti (LPPM Stikes Jenderal Achmad Yani Cimahi, 2021)
The results of the community satisfaction survey and analysis of community satisfaction with services at the Cikalongwetan DPT Puskesmas obtained an average index of 2.89%. This shows that in general service performance still does not meet good service quality. The purpose of this study was to determine the relationship of service quality with inpatient satisfaction at the Cikalongwetan DPT Community Health Center in 2019. The sample in this study was 77 respondents, patients who received inpatient services. This type of research is quantitative analytic survey research method with cross sectional approach. Data collection techniques using a questionnaire. Analysis of the study used the chi square statistical test. The results obtained are that there is a relationship between service quality and inpatient satisfaction at the Cikalongwetan DPT Puskesmas with a p value of 0,000. There is a relationship between the quality of responsiveness with satisfaction of inpatients with a p value of 0.039. There is a relationship between the quality of empathy with empathy satisfaction of inpatients with a p value of 0.004. Suggestions for puskesmas to maintain and improve the overall quality of hospitalization so that people want to take advantage of existing health services in puskesmas